2012
DOI: 10.1021/ma300686b
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Cyclization in A2 + B3 Polymers via Step-Wise Polymerization Resulting in a Highly Branched Topology: Quantitative Determination of Cycles by Combined NMR and SEC Analytics

Abstract: In this contribution, we report a convenient expression of average number of cyclic structures (ANC) and cyclic-average molecular weight (M C ) to quantificationally describe the topological defect of intramolecular cyclization in highly branched polymers synthesized via A 2 + B n (n ≥ 3) stepwise polymerization strategy by a combination of nuclear magnetic resonance spectrometry (NMR) and size exclusion chromatography (SEC). The ANC and M C depend on the number ratio of dendritic, linear, terminal units and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 59 publications
1
48
0
Order By: Relevance
“…S2 (Supplementary Information). The Mark-Houwink-Sakurada (MHS) exponent is a parameter corresponding to the topology of a polymer in a good solvent [31]. Generally, for hyperbranched polymers, the exponent typically varies from 0.5 to 0.2.…”
Section: Molecular Structure Analysis Of Hbpsimentioning
confidence: 99%
“…S2 (Supplementary Information). The Mark-Houwink-Sakurada (MHS) exponent is a parameter corresponding to the topology of a polymer in a good solvent [31]. Generally, for hyperbranched polymers, the exponent typically varies from 0.5 to 0.2.…”
Section: Molecular Structure Analysis Of Hbpsimentioning
confidence: 99%
“…The first step was the hydrosilylation of the vinyl groups, which gave an explanation to the disappearance of vinyl groups and the decrease in the intensity of Si–H bonds. As the hydrosilation procedure started at 200 °C, almost no change for the intensities of the vinyl and Si–H vibrations were observed in PSBN138. However, the addition of [Co(en) 3 ]·Cl 3 to PSBN1 induced the disappearance of the absorption bands of the alkanes, which demonstrated that the [Co(en) 3 ]·Cl 3 acted as a catalyst for the hydrosilylation.…”
Section: Resultsmentioning
confidence: 98%
“…Among these strategies, A 2 +B 3 ‐type DMM has been widely used to construct the hyperbranched topology. By regulating the feed ratio, Chen et al . outline the synthesis of two kinds of HPs to analyze the degree of intramolecular cyclization.…”
Section: Hyperbranched Topology Constructionmentioning
confidence: 99%